The challenges of Bumiputera furniture SME in design capabilities - Osman, Nur Syazana; Abd Rahman, Khairul Aidil Azlin; Abdul Rahman, Ahmad Rizal; Zaky Ja'afar, Mohamad Fakri (RMP Publications, 2019)
In the furniture industry in Malaysia, the factors that influence the export value of Bumiputera furniture SME manufacturers have already been discussed, and with the lack of clusters that could continue the survival of Bumiputera manufacturers in this industry is getting worse. Although the furniture sector has the highest export value, the participation of Bumiputera furniture SME is very low compared to others. This is disrupted as the current Bumiputera furniture SME is incapable, due to the increasing competition or weakness in different aspects of entrepreneurship and other factors, to continue the business sustainability. This article aims to discuss the design capabilities that affect the performance of Bumiputera furniture SME manufacturers and how to overcome through strategic design approaches. In this study, a set of questionnaire was distributed to 30 companies and analyzed using the IBM Social Sciences Statistical Package (SPSS) to test the reliability. The further analysis was the use of frequency analysis and principal component analysis (PCA). The results have important implication for the future direction of research to improve organizational performance of Bumiputera furniture SME manufacturers.